THE INFLUENCE OF ESG, STRATEGIC SUSTAINABILITY MANAGEMENT, COMPETITIVE ADVANTAGE, AND GOVERNANCE ON FIRM VALUE - Aprillida, Thasya; Astuti, Christina Dwi; Wahyuni, Endah Sri (JURNAL INFORMASI, PERPAJAKAN, AKUNTANSI, DAN KEUANGAN PUBLIK, 2025)
This study explores the effects of Environmental, Social, and Governance (ESG) disclosure, strategic sustainability management, competitive advantage, the presence of independent commissioners, and foreign ownership on firm value. The research focuses on a purposively selected sample of 60 firms within the mining and energy sectors. Secondary data were obtained from annual and sustainability reports issued between 2021 and 2023, sourced from the official websites of the respective companies and the Indonesia Stock Exchange (IDX). Utilizing a quantitative research design and multiple linear regression analysis, the results indicate that all five variables have a positive impact on firm value. These findings emphasize the significant role of sustainable business practices in driving corporate value, highlighting the need for companies to maintain transparent and consistent integration of sustainability within their business operations.